ASPEKTY PRAWNE ZABIEGÓW KOSMETYCZNYCH WYKONYWANYCH PRZEZ KOSMETOLOGA - Banaś, Sylwia (Kwartalnik Prawa Publicznego, 2016)
This article is devoted to the legal aspects of cosmetic procedures performed by a cosmetolo-gist. Firstly it describes the terms of reference of professional cosmetologists. Next, attention was paid to the legal aspect of cosmetologist profession, and it was proposed to put it among the medical profession. Then the author tries to answer the question whether, on the basis of existing legislation, invasive cosmetic treatments performed by a cosmetologist are legal. Laser treatment trainings have also been assessed. In the end criminal and civil liabilities on the field cosmetic treatments have been considered. The author, basing on all elements of the subject, presents currently practised solutions. These considerations are also a review of the positions of doctrine and juris-prudence in the discussed area.